Modeling flood impact on residential property value - Hassim, Muhammad (2022)
In the context of the property market in Malaysia, environmental impact such as flooding is not clearly stated in the value of the property. It has not yet been ascertained whether flood factor affects buyer's preference and is taken into consideration in residential property transactions. This research examined the effect of flood on house price with special attention in high density areas such as Kajang city area in Langat River Basin, Malaysia. It aims to develop a flood impact model to assess the impact of flood on property value. This study used XP-Storm Water Management Model (XP-SWMM) software to establish a two-dimension (2D) flood map as well as the inundation area of the flood, and Statistical Package for the Social Science (SPSS) software to identify the relationship between the house value and flooding factor. The data include the property transaction from 2013 to 2018 and hydrological data such as precipitation and discharge (m3/s) in the study area. Property transaction data from Valuation and Property Services Department was analysed using Pola Graph and Multiple Regression Analysis in SPSS. The simulation model was developed for Kajang city area. The flood simulation produced a streamflow graph that subsequently used in property impact assessment analysis. As an overall comparison, the peak flow and the shape of the hydrograph for the calibration and validation works are in good agreement. The study indicates that flooding always has a negative impact on property value, which the results showed a decrement in value by 7% on average every year starting from 2013 to 2018. There is also a slight difference in value between property in flood free and flood liable areas. This flood model impact provides a concrete assessment of the flood impact on property value, and such data is useful to guide professionals to determine the property value in flood-prone areas and also to potential buyers in making an informed decision in real estate investment.